2010
DOI: 10.5152/jtgga.2010.07
|View full text |Cite
|
Sign up to set email alerts
|

Shortening the second stage of labor?

Abstract: Application of uterine fundal pressure in a delivering woman was not only ineffective in shortening the second stage of labor but added to the risks during parturition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
7
0
3
Order By: Relevance
“…Em um dos relatos a parturiente descreve que em sua primeira gestação, durante o trabalho de parto, dois médicos teriam subido sobre seu abdômen, usando de força com o intuito de acelerar a expulsão do concepto. Contudo, um estudo evidencia que a pressão exercida no Research, Society and Development, v. 9, n. 7, e934975086, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.5086 8 fundo do útero não se mostra eficaz com o objetivo de reduzir o tempo do segundo momento do parto, além disso, eleva a taxa de episiotomia, retenção de placenta, fraturas e danos ao recém-nascido (Mahendru, 2010).…”
Section: Resultsunclassified
“…Em um dos relatos a parturiente descreve que em sua primeira gestação, durante o trabalho de parto, dois médicos teriam subido sobre seu abdômen, usando de força com o intuito de acelerar a expulsão do concepto. Contudo, um estudo evidencia que a pressão exercida no Research, Society and Development, v. 9, n. 7, e934975086, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.5086 8 fundo do útero não se mostra eficaz com o objetivo de reduzir o tempo do segundo momento do parto, além disso, eleva a taxa de episiotomia, retenção de placenta, fraturas e danos ao recém-nascido (Mahendru, 2010).…”
Section: Resultsunclassified
“…Applying fundal pressure has been both recommended and condemned as a strategy for assisting birth in the management of shoulder dystocia [14, 15]. To our knowledge, the only published randomized controlled trials (RCTs) of manual fundal pressure during vaginal birth have found no benefits associated with its use, but the numbers studied were small [16, 30]. A pilot RCT of manual fundal pressure compared with standard care in 209 nulliparous women with uncomplicated pregnancies in a hospital in India found no significant reduction in the duration of the second stage of labour, but an increase in perineal injuries [16].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the only published randomized controlled trials (RCTs) of manual fundal pressure during vaginal birth have found no benefits associated with its use, but the numbers studied were small [16, 30]. A pilot RCT of manual fundal pressure compared with standard care in 209 nulliparous women with uncomplicated pregnancies in a hospital in India found no significant reduction in the duration of the second stage of labour, but an increase in perineal injuries [16]. A 2005 review of the manoeuvre concluded that the role of fundal pressure is understudied and caution should be exercised until it is proven to be safe and effective [11].…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de pesquisas recentes não demonstrarem benefícios na realização da pressão no fundo uterino no momento do período expulsivo (manobra de Kristeller), esta intervenção é comumente utilizada durante o cuidado prestado ao parto, principalmente com o intuito de encurtar o segundo período do parto (MATSUO et al, 2009;API et al, 2009;MAHENDRU, 2010;SARTORE et al, 2012). O Kristeller não possui respaldo científico suficiente para sua realização rotineira nos serviços.…”
Section: Objetivos Específicosunclassified
“…Esta prática possui grandes riscos a desfechos desfavoráveis e demonstra ser ineficaz, devendo não ser realizada nas mulheres (MATSUO et al, 2009;MAHENDRU, 2010;SARTORE et al, 2012). Revisão sistemática realizada com um único estudo envolvendo 500 mulheres teve como objetivo comparar o uso da pressão do fundo uterino, por meio de um cinto inflável, com a não realização desta intervenção.…”
Section: Objetivos Específicosunclassified